2017
DOI: 10.1016/j.forsciint.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Sharp and blunt force trauma concealment by thermal alteration in homicides: An in-vitro experiment for methodology and protocol development in forensic anthropological analysis of burnt bones

Abstract: Burning of human remains is one method used by perpetrators to conceal fatal trauma and expert opinions regarding the degree of skeletal evidence concealment are often disparate. This experiment aimed to reduce this incongruence in forensic anthropological interpretation of burned human remains and implicitly contribute to the development of research methodologies sufficiently robust to withstand forensic scrutiny in the courtroom. We have tested the influence of thermal alteration on pre-existing sharp and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 57 publications
5
29
0
Order By: Relevance
“…Previous literature showed that sharp force trauma on a bone could survive the bone being burned [26, 32-34, 38, 59]. It is highlighted that morphological changes to the trauma could occur because of the burning; hence, further research is necessary [30,[32][33][34][35][36]. Similarly, all the cut marks in this study were grossly identifiable after burning, despite the bone sample fracturing, with a small number of fractures intersecting cut marks.…”
Section: Post-burningmentioning
confidence: 50%
See 3 more Smart Citations
“…Previous literature showed that sharp force trauma on a bone could survive the bone being burned [26, 32-34, 38, 59]. It is highlighted that morphological changes to the trauma could occur because of the burning; hence, further research is necessary [30,[32][33][34][35][36]. Similarly, all the cut marks in this study were grossly identifiable after burning, despite the bone sample fracturing, with a small number of fractures intersecting cut marks.…”
Section: Post-burningmentioning
confidence: 50%
“…Defined by location and direction of fracture propagation, heat-induced fractures can be categorised as longitudinal, transverse, curved transverse, delamination, and patina [32]. Heat-induced fractures and fragmentation can be recognisable, but they may be confused also with skeletal perimortem trauma because their features mimic or obscure antecedent traumatic characteristics [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…All specimens were macerated on the same day of purchase in the UCL Bioarchaeology Laboratory utilizing manual de‐fleshing and hot water enzyme maceration [27,28]. In an attempt to enhance experimental replicability [29] specimens were macerated prior to sectioning. Defleshed porcine bones have previously been used in tool mark analysis research [13,21,30].…”
Section: Methodsmentioning
confidence: 99%